A Meta-Analysis: The Effect of Emotional Intelligence on Students' Mathematics Learning Outcomes in Indonesia - Aljura, Ahmad Naufal; Retnawati, Heri; Widjajanti, Djamilah Bondan (Jurnal Riset Pendidikan Matematika, 2024)
This study aimed to determine the effect size of emotional intelligence on student learning outcomes in Mathematics learning, described research trends based on categories, and described emotional intelligence scales (instruments) used in Mathematics learning. This research used a quantitative approach with the method of Systematic Literature Review with Meta-Analysis. The data collected for the qualitative descriptive were 14 research articles and for the combined effect size analysis were 11 articles. It was found that the research trend on the effect of emotional intelligence on Mathematics learning outcomes has increased from 2015 to 2022. The results of the analysis showed that the significant effect of Emotional Intelligence on students' Mathematics learning outcomes was categorized as " medium impact". For the category of education level, junior high school has the highest combined effect value (1.120) in its subgroup, which is categorized as "very high impact". For the demographic category, Kalimantan, Nusa Tenggara, and Maluku regions have the highest combined effect value (0.806) in their subgroups categorized as "high impact". For the type of emotional intelligence scale, articles with standardized (0.659) and unspecified (0.698) scales have relatively the same effect categorized as "medium impact", and the dominance of its use is based on Solovey and Mayer.